2016
DOI: 10.1002/lno.10284
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of reservoir methane emissions based on a spatially balanced probabilistic‐survey

Abstract: Global estimates of methane (CH 4 ) emissions from reservoirs are poorly constrained, partly due to the challenges of accounting for intra-reservoir spatial variability. Reservoir-scale emission rates are often estimated by extrapolating from measurement made at a few locations; however, error and bias associated with this approach can be large and difficult to quantify. Here, we use a generalized random tessellation survey (GRTS) design to generate unbiased estimates of reservoir-CH 4 emissions rates (695% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 48 publications
6
63
4
Order By: Relevance
“…By comparison, ebullition at transects T2 and T3, which are just downstream of FCR's primary inflow, was driven by variables characteristic of riverine and transitional sites in larger reservoirs (Beaulieu et al, ). Ebullition rates at both T2 and T3 sites were driven by a negative association with inflow discharge, and ebullition at T2 also had a positive association with SWI temperature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By comparison, ebullition at transects T2 and T3, which are just downstream of FCR's primary inflow, was driven by variables characteristic of riverine and transitional sites in larger reservoirs (Beaulieu et al, ). Ebullition rates at both T2 and T3 sites were driven by a negative association with inflow discharge, and ebullition at T2 also had a positive association with SWI temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Within reservoirs, CH 4 ebullition and diffusion rates can vary substantially along a longitudinal gradient from the upstream areas near the major inflows to the downstream areas near the dam (Beaulieu et al, , ; Huang et al, ; Sobek et al, ; Tušer et al, ). Ebullition is generally highest in shallow areas upstream, with much lower (but still detectable) rates in downstream areas (Beaulieu et al, , ). Similarly, studies have also demonstrated that the highest diffusion rates occur in shallow upstream sites and decrease toward the deeper sites in larger reservoirs (Beaulieu et al, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations